Effect of invasive ctenophores Mnemiopsis leidyi and Beroe ovata on low trophic webs of the Black Sea ecosystem. (April 2019) - Shiganova, T.A.; Mikaelyan, A.S.; Moncheva, S.; Stefanova, K.; Chasovnikov, V.K.; Mosharov, S.A.; Mosharova, I.N.; Slabakova, N.; Mavrodieva, R.; Stefanova, E.; Zasko, D.N.; Dzhurova, B.
Abstract: The study focuses on the impact of life excretion and mucus released by the "biological pollutants" invasive ctenophore Mnemiopsis leidyi and its predator Beroe ovata on the marine environment and lower trophic levels of the Black Sea ecosystem (bacteria, pico-phytoplankton, nano-autotrophic/heterotrophic flagellates, micro-phytoplankton, chlorophyll a, primary production (PP), micro-zooplankton). The chemical and biological variables were analysed in two sets of lab experiments with natural communities from mesotrophic (Gelendzhik) and eutrophic (Varna) coastal waters. While both species altered the chemical properties of experimental media, exerting structural and functional changes in the low food-web biological compartments, the results showed a stronger effect of B. ovata, most likely related to the measured higher rate of excretion and amount of released mucus. In addition the alterations in the Gelendzhik experiment were more pronounced, indicating that environmental implications on lower food-web are more conspicuous in mesotrophic than in eutrophic coastal waters. Highlights: Experiments with invasive ctenophores in the NW and NE shelves of the Black Sea Life excretions and mucus secretion of Mnemiopsis leidyi and Beroe ovata Both ctenophores induced alterations in phytoplankton, chlorophyll and primary production Both ctenophores caused changes in bacteria and micro-zooplankton biomass The effect has been observed much more remarkable in Gelendzhik mesotrophic area.